Nationalism and national integration - Birch, Anthony Harold (Unwin Hyman, 1989)
A concise and stimulating analysis of the theory of nationalism, and the theories, process and problems of national integration. Although nationalism is the most successful political ideology in human history, its achievement in getting the world's entire land surface divided between nation-states has led to considerable problems in integrating the ethnic and cultural minorities within these states.
Keywords: Nationalism.; Nation-state.; Nationalisme.; Nation.; nationalism.; nations.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism.; Nation-state; Nationalism